2011
DOI: 10.7150/jca.2.503
|View full text |Cite
|
Sign up to set email alerts
|

Cavitary Lung Cancer Lined with Normal Bronchial Epithelium and Cancer Cells

Abstract: Reports of cavitary lung cancer are not uncommon, and the cavity generally contains either dilated bronchi or cancer cells. Recently, we encountered a surgical case of cavitary lung cancer whose cavity tended to enlarge during long-term follow-up, and was found to be lined with normal bronchial epithelium and adenocarcinoma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…A previous report suggested that traction ectasia of the conducting airway caused by fibrosis was one of the mechanisms of formation of thin-walled cavitary lung cancer [2], indicating that the actual thin-walled cavity is formed because of tumor-related collapsed fibrosis. In our study, approximately 17% of cases exhibited combined type cavity linings; similar cases of cavitary adenocarcinoma with internal cavity surfaces being lined with dilated bronchial and adenocarcinoma cells have been reported [5,17]. These results suggest that a combination of tumor destruction and bronchial dilation due to tumor-related collapsed fibrosis may be one of the causes of cavity formation.…”
Section: Commentsupporting
confidence: 87%
“…A previous report suggested that traction ectasia of the conducting airway caused by fibrosis was one of the mechanisms of formation of thin-walled cavitary lung cancer [2], indicating that the actual thin-walled cavity is formed because of tumor-related collapsed fibrosis. In our study, approximately 17% of cases exhibited combined type cavity linings; similar cases of cavitary adenocarcinoma with internal cavity surfaces being lined with dilated bronchial and adenocarcinoma cells have been reported [5,17]. These results suggest that a combination of tumor destruction and bronchial dilation due to tumor-related collapsed fibrosis may be one of the causes of cavity formation.…”
Section: Commentsupporting
confidence: 87%
“…a−e), the central cavity seems to represent dilated bronchi or mucus lakes. However, cavity formation also occurs in peripheral adenocarcinomas . Therefore, cavity formation is not a specific finding in CMPT.…”
Section: Discussionmentioning
confidence: 94%
“…Cavitation in lung cancer can be found in 2-16% of diagnosed cases [4]. The walls of ca- vities are usually thicker than 4 mm [5].…”
Section: Discussionmentioning
confidence: 99%